Pengembangan Aplikasi Media Pembelajaran Sejarah Kebudayaan Islam Berbasis Android di Madrasah Tsanawiyah - Fauziah, Zumrotul; Rahmawati, Ulva Badi'; Pratama, Angga (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to explain the design system for the Android-based Cultural History learning application in class IX MTs Miftahul Ulum Sitiaji Bojonegoro, East Java. This research was conducted with a research and development model. Where researchers create and design products in the form of an Android-based Appy Pye application. The results showed; 1) the teacher prepares materials, videos, and pictures; 2) develop the application by logging into the Appy Pye web using a Gmail, email, or Facebook account, filling in what application is made, editing the application start page, and select the menu as desired, prepare Appy Pye and an international account for filling in personal data, download the application and fill in the desired material, and do the application test stage. 3) The Android-based Appy Pye application can increase student learning motivation in Islamic Cultural History subjects.